Role of diagnostic laparoscopy in chronic abdominal conditions with uncertain diagnosis - Rao, T. Uma Maheswara (International Surgery Journal, 2016)
Background:The aim of the study is to evaluate the benefits of diagnostic laparoscopy in cases of chronic abdominal conditions with uncertain diagnosis; this study was conducted that it might obviate the need for imaging techniques in establishing the final diagnosis of these conditions. Methods: This study was conducted in 150 patients in Department of Surgery with uncertain diagnosis after five weeks of onset of symptoms was patients who had history of abdominal pain for 3 months or more, if physical examination and diagnostic tests are unrevealing, previous history of abdominal operation. Laparoscopy was performed after completion of all the necessary hematological, biochemical, radiological, and ascetic fluid analysis, gastrointestinal endoscopic and imaging techniques, and Mantoux test. Results:This study was done in 150 patients who had chronic abdominal pain showed peak incidence in 3rd decade and the age group of 18-25 had the highest percentage of 30%. Males were 52 and females were 98. Duration of pain in laparoscopy was the highest in 15-25 weeks. Lower abdomen had more number of cases i.e 100. Findings during laparoscopy were highest in appendicitis. Conclusions:Laparoscopy is considered an effective therapeutic and used in diagnosis of management of patients with abdominal pain.